Design and analysis of a lightweight beam-type topologically interlocked material system. (May 2023) - Laudage, Steven; Guenther, Ethan; Siegmund, Thomas
Abstract: Topologically interlocked material systems are assemblies of interlocking building blocks which exhibit advantageous combinations of strength and toughness under transverse load. In general, the structural efficiency of structural members carrying a transverse load can be modulated by shaping the cross-section. This study provides novel insights into the effectiveness of material removal on the mechanical behavior of a beam-type topologically interlocked material system. A reference configuration with solid building blocks is established and its response is investigated by experiments and finite element analysis (FEA) models. A parametric investigation combining several approaches for material removal with a range of relative material densities is conducted, and the response of resulting assemblies is reported. The force–displacement behavior and the load transfer of the reduced weight systems are compared to the solid reference system and to that of an extruded box beam. Results show that lintels made with material-removed blocks retain the general load–deflection response characteristics of lintels made from solid building blocks, despite significant changes to the load transfer pattern internally. Material removal approaches exist such that the lintel retains the mass-specific mechanical properties of the solid structure.